Nurses' intentions to respond to requests for legal assisted‐dying: A Q‐methodological study. (26th November 2019) - Wilson, Michael R.; Wiechula, Rick; Cusack, Lynette; Wilson, Marie
Abstract: Aims: To explore the intentions of nurses to respond to requests for legal assisted‐dying. Background: As more Western nations legalize assisted‐dying, requests for access will increase across clinical domains. Understanding the intentions of nurses to respond to such requests is important for the construction of relevant policy and practice guidelines. Design: Mixed‐methods. Data Sources: A total of 45 Australian nurses from aged, palliative, intensive, or cancer care settings surveyed in November 2018. Method: Q‐methodology studying nurses' evaluations of 49 possible responses to a request for a hastened death. Data consisted of rank‐ordered statements analysed by factor analysis with varimax rotation. Findings: Four distinct types of intentions to respond to requests for assisted‐dying: a) refer and support; b) object to or deflect the request; c) engage and explore the request; or d) assess needs and provide information. Conclusion: The findings underscore the complexity of intentionality in assisted‐dying nursing practice and differences from other forms of end‐of‐life care, particularly regarding patient advocacy and conscientious objection. This study enables further research to explore determinants of these intentions. It can also assist the development of professional guidance by linking policy and clinical intentions. Impact: Identified a basic range of nurses' intentions to respond to requests for assisted‐dying, as there was no evidence at present. Developed a fourfold typology of intentions to respond with most nurses intending to engage in practices that support the requestor and sometimes the request itself. A minority would object to discussing the request. The relatively low level of advocacy within the intended responses selected also is distinctly different from other end‐of‐life care research findings. This research could assist nursing associations in jurisdictions transitioning to legal assisted‐dying to develop guidance ways nurses can frame their responses to requests. Abstract : 目的: 探讨护士对合法安乐死请求的回应意图。 背景: 随着越来越多的西方国家将安乐死合法化, 临床领域对安乐死的要求将会增加。了解护士回应此类要求的意图对于相关政策和实践指南的构建具有重要意义。 设计: 混合方法。 数据来源: 2018年11月, 共有45名来自老年、姑息治疗、强化治疗或癌症护理环境的澳大利亚护士接受了调查。 方法: Q‐方法学研究护士对加速死亡请求的49种可能反应的评估。数据由等级顺序的报表组成, 通过因素分析和正交旋转法进行分析。 研究结果: 四种不同类型的意图回应协助死亡的请求:a)提及和支持;b)反对或转移请求;c)参与和探讨请求;或d)评估需求和提供信息。 结论: 研究结果强调了辅助临终护理实践中意图性的复杂性, 以及与其他临终护理形式的差异, 特别是在病人的倡导和出于良心上的反对。这项研究使得进一步的研究能够探索这些意图的决定因素。它还可以通过将政策和临床意图联系起来来协助专业指导的发展。 影响: 虽目前尚无证据, 但研究确定了护士对安乐死请求作出回应的意图的基本范围。开发了一个四重类型的意图回应, 旨在使大多数打算参与支持请求者甚至有时请求本身实践的护士做出回应。少数人反对讨论这项请求。少数将反对讨论该请求。在选定的预期反应中, 相对较低的倡导水平也明显不同于其他临终护理研究结果。本研究可协助过渡到合法安乐死的地区的护理协会发展护理人员对安乐死请求回应的指导方法。